9x-8y=-67

Simple and best practice solution for 9x-8y=-67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-8y=-67 equation:


Simplifying
9x + -8y = -67

Solving
9x + -8y = -67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8y' to each side of the equation.
9x + -8y + 8y = -67 + 8y

Combine like terms: -8y + 8y = 0
9x + 0 = -67 + 8y
9x = -67 + 8y

Divide each side by '9'.
x = -7.444444444 + 0.8888888889y

Simplifying
x = -7.444444444 + 0.8888888889y

See similar equations:

| 19.5-x=7.2 | | 12x^2+24+5=4x+5 | | y=x+x+20 | | 7x+14y=49 | | 8(-7)=6(-7)-14 | | 2.5(1-x)=1 | | 4(3-u)=u+22+2u | | -8=-4n+8 | | 10+13y=1 | | 5(1-3a)=-85 | | y=177.46x-7e+06 | | 225y-80x=0 | | 108=3(-8+4x) | | 3x^2-12=-39 | | (X+4)(6)(x)=840 | | 4x^2-12x-12y+21=0 | | 6(6+3r)=108 | | 1/5x-18=2 | | 19.5-7.2=x | | 1/7x-3=6 | | 21+3c-7(2-3c)=4(c-5)+3c+27 | | 15(4n-4)=-60 | | 2(x-6)+2=9x-(7x+6)-4 | | 7/2x=3/x-5 | | 15=t/4-1 | | 6n+1=2n+1 | | 3v-8=7+2v-v | | 3(x+4)-5=4x-(2x+3) | | V-7=40 | | 2(x+4)-2=4x-(3x+2) | | 13x-9=-2(-4x-3) | | 3/4m=75 |

Equations solver categories